A new species of Xylota Meigen (Diptera: Syrphidae) from the Far East - Mutin, Valerii; Ichige, Katsuyoshi (Zootaxa, 2014)
Xylota danieli Mutin & Ichige spec. nov. is proposed as the new name for Xylota amamiensis Shiraki sensu Mutin & Gilbert (1999), from the Russian Far East and Japan, which is described and figured. New synonymy is proposed for Xylota coquilletti Hervé-Bazin, 1914 (= X. coquilletti amamiensis Shiraki, 1968 syn. nov.; = X. vulgaris Yang & Cheng in Cheng & Yang, 1993 syn. nov.).